Aboriginal parent support: A partnership approach - Munns, Ailsa; Toye, Christine; Hegney, D.; Kickett, Marion; Marriott, R.; Walker, R. (Wiley-Blackwell Publishing, 2018)
AIMS AND OBJECTIVES: This study was positioned within a larger action research study relating to a peer-led Aboriginal home visiting parent support program in an urban Western Australian setting. The aims for this study component were to identify program elements, exploring participants' perceptions of the program's suitability, feasibility, acceptability and effectiveness to inform program model recommendations and add to the body of knowledge on effective Aboriginal peer-led program models. BACKGROUND: The ability of Aboriginal parents to develop positive family environments is crucial, with parent support needing to be reflexive to local needs and socio-cultural influences. Culturally appropriate service provision needs meaningful and acceptable strategies. DESIGN: This study was situated within a critical paradigm supporting Participatory Action Research methodology, using Action Learning Sets as the participant engagement and data collection setting. METHODS: Within ten Action Learning Sets, focus group interviews were carried out with Aboriginal peer support workers, a non-Aboriginal parent support worker, an Aboriginal program coordinator, an Aboriginal education support officer and non-Aboriginal program managers, (n=8), and individual interviews with parents (n=2) and community agencies (n=4). Data were analysed using thematic analysis. RESULTS: Five themes were derived from peer support worker and community agency cohorts: Peer support worker home visiting skills; Responding to impacts of social determinants of health; Client support and engagement; Interagency collaboration, and Issues addressing program sustainability. Parent responses augmented these themes. CONCLUSIONS: Participants identified five key elements relating to peer-led home visiting support for Aboriginal parents. These are uniquely placed to inform ongoing program development as there is little additional evidence in wider national and international contexts.